2018
DOI: 10.1088/1361-6420/aad7cd
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian framework for molecular strain identification from mixed diagnostic samples

Abstract: We provide a mathematical formulation and develop a computational framework for identifying multiple strains of microorganisms from mixed samples of DNA. Our method is applicable in public health domains where efficient identification of pathogens is paramount, e.g., for the monitoring of disease outbreaks. We formulate strain identification as an inverse problem that aims at simultaneously estimating a binary matrix (encoding presence or absence of mutations in each strain) and a real-valued vector (represent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…A previously developed mathematical algorithm, StrainRecon [ 17 ], was used for identifying haplotypes and enumerating strains based on frequency results of individual 24-SNP barcodes generated from NGS. Briefly, the basic StrainRecon algorithm accepts a vector of SNP frequencies as input and a parameter n denoting the anticipated number of strains.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previously developed mathematical algorithm, StrainRecon [ 17 ], was used for identifying haplotypes and enumerating strains based on frequency results of individual 24-SNP barcodes generated from NGS. Briefly, the basic StrainRecon algorithm accepts a vector of SNP frequencies as input and a parameter n denoting the anticipated number of strains.…”
Section: Methodsmentioning
confidence: 99%
“…Whole genome deep sequencing has improved MOI estimation at the population level by detecting genomic signatures and minority strains of parasites through newly developed analytical tools, StrainRecon [ 17 ] and DEploid [ 18 ]. The main difference between StrainRecon and DEploid is that DEploid requires a reference panel of strains to be provided as a prior for potential haplotypes present in the sample, whereas StrainRecon, discussed below, requires no templates or priors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These proportions can be used to group alleles from different genes by their strain of origin. This concept is illustrated in Figure 2 and one potential implementation is described in Mustonen et al (2018). This approach may also distinguish whether reads generated from mutational AMR determinants belong to the pathogen or background bacteria since studies have shown that health adults carry AMR genes in their gut microflora (Fitzpatrick and Walsh, 2016).…”
Section: Amplicon Sequencingmentioning
confidence: 99%